Adjuvant chemotherapy versus surgery alone for esophageal squamous cell carcinoma: a meta-analysis of randomized controlled trials and nonrandomized studies. Issue 6 (1st August 2014) - Zhang, S.-S.; Yang, H.; Xie, X.; Luo, K.-J.; Wen, J.; Bella, A. E.; Hu, Y.; Yang, F.; Fu, J.-H.
Summary: The effect of adjuvant chemotherapy on survival of patients with thoracic esophageal squamous cell carcinomas is still controversial, and the subgroup of patients who will most likely benefit from the adjuvant chemotherapy on long-term survival has not yet been identified clearly. Studies published from 1995 to M ay 2012 were searched in M edline, E mbase, PubMed, C ancerlit, the C ochrane L ibrary, CNKI and major scientific meetings. Randomized controlled trials and nonrandomized studies comparing surgery plus adjuvant chemotherapy with surgery alone in patients with resectable thoracic esophageal squamous cell carcinomas were included. Eleven studies with a total of 2047 patients were identified, consisting of the adjuvant chemotherapy arm ( n = 887) and surgery-alone arm ( n = 1160). There was not statistically significant benefit on 3-year overall survival for adjuvant chemotherapy (risk ratio [RR ] = 0.89, 95% confidence interval [CI ], 0.72 to 1.09; P = 0.25). Adjuvant chemotherapy could significantly prolong the 1-year disease-free survival (DFS ) (RR = 0.68, 95%CI, 0.51 to 0.89; P = 0.006), but not 3-year DFS (RR = 0.97, 95%CI, 0.73 to 1.29; P = 0.84). Further analysis showed that patients with stage III-IV diseases could benefit from adjuvant chemotherapy on 3-year overall survival (RR = 0.43, 95%CI, 0.31 to 0.61; P = 0.00001), but not in the case of patients with stageI-IIdiseases (RR = 1.12, 95%CI, 0.65 to 1.93; P = 0.68). Additionally, patients with positive lymph node could benefit on 5-year DFS from adjuvant chemotherapy (RR = 0.79, 95%CI, 0.64 to 0.99; P = 0.04). The modality treatment with adjuvant chemotherapy for patients with squamous cell carcinoma of thoracic esophagus might be determined according to pathological stage or the status of lymph node metastasis.